Preliminary results on the simulation of the 1999 Orissa super cyclone using a GCM with a new boundary layer code - VENKATESH, T. N.; MUDKAVI, VIDYADHAR; RAJALAKSHMY, S.; SARASAMMA, V. R.; SINHA , U. N.; NARASIMHA, R. (MAUSAM, 2006)
& bl ’kks/k&Ik= esa ,u- ,e- vkbZ- Vh- ,y- vkbZ- ifj;kstuk ds ,d Hkkx ds :Ik esa fy[ks x, ,d u, ,- th- lh- ,e- dksM+ ¼uker% o"kkZ½ dk mi;ksx djrs gq, mM+hlk ds egkpØokr ds izfr:i.k ls izkIr fd, x, izkjfEHkd ifj.kkeksa dks izLrqr fd;k x;k gSA bZ- lh- ,e- MCY;w- ,Q- Vh-&106 dh vkjfEHkd voLFkkvksa dk mi;ksx djrs gq, 26 vDrwcj] 1999 dks 0000 ;w- Vh- lh- ij bl izfr:i.k dks vkjEHk fd;k x;k gSA gok ds >ksadsiu ds dkjd dks lfEefyr djrs gq, ekud eksuhu&vkscw[kkso ifjlhek Lrj dksM ls Vh&80 ds foHksnu ij o"kkZ dksM dk mi;ksx djrs gq, daVªksy ju fd;k x;k gSA 78 fd-eh- xzhM varjky ls 120 LisDVªy ekWMl esa mUur kSfrt foHksnu vkSj eUn iouksa ij u, ifjlhek Lrj ds izkpyhdj.k ls dksM vla[; o`f);ksa dks n’kkZrk gS% izfr:i.k dks vkjEHk djus ds i’pkr vf/kdre =qfV esa 36 ?kaVksa dh vof/k esa 350 ls 234 fd-eh-] 48 ?kaVksa dh vof/k esa 310 ls 34 fd-eh- vkSj 96 ?kaVksa dh vof/k esa 410 ls 55 fd-eh- rd =qfV;ksa dh vf/kdre deh ikbZ xbZ gSA blesa ;g lq>ko fn;k x;k gS fd bl o`f) dk Js; i`"Bh; cyksa ds mUur vkdyu vkSj u, ifjlhek Lrj cy vk?kw.kZ ¼VkdZ½ dksM esa fufgr gSA blesa cy vk?kw.kZ ¼VkdZ½ dh Hkwfedk izeq[k ;ksxnku ds :Ik esa gh gS tksfd fo’ks"k :i ls pØokrksa dh i`"B Hkwfe ls lacaf/kr gSa tgk¡ ij iousa rqyukRed :i ls gYdh gksrh gSa fdarq ml ks= esa fo|eku i`"Bh; cy rFkk bldh vk?kw.kZ Hkqtk ¼ewesaV vkeZ½ nksuksa vf/kd gksrh gSaA vk’p;Ztud :Ik ls mPprj i`"Bh; cy u, dksM kjk iwokZuqekfur mPprj iouksa ls Hkh mRiUu gksrs gSaA blesa jkspd ckr ;g gS fd bldh i`"B Hkwfe pØokr ds ekxZ vkSj U;wure vonkc nksuksa esa u, ifjlhek Lrj ekM;wy ls mPprj foHksnu ds dkj.k gqbZ o`f) ls cgqr vf/kd lacaf/kr gSA pØokr iFk iwokZuqeku ij vU; Hkaoj ¶yDlksa ¼laos| m"ek] vknzZrk½ ds izHkko dk ewY;k¡du djus ds fy, vkSj vf/kd fo’ys"k.k djuk vko’;d gSA We present here preliminary results from the simulation of the Orissa super cyclone using a new AGCM code (named Varsha) written as part of a NMITLI project. The simulation is initialized at 0000 UTC, 26 October 1999, using ECMWF T-106 initial conditions. The control run is made using the Varsha code at a T-80 resolution with a standard Monin-Obukhov boundary layer code incorporating a gustiness factor. With the horizontal resolution improved to 120 spectral modes with a 78 km grid spacing, and a new boundary layer parameterization at low winds, the code shows substantial improvements: the maximum error is reduced from 350 to 234 km at 36 hr after initialization, 310 to 34 km at 48 hr, and 410 to 55 km at 96 hr. It is suggested that part of the explanation for this improvement lies in the improved estimation of surface forces and torque in the new boundary layer code. The role of torque is particularly interesting as the major contribution to it comes from the outer regions of the cyclone where the winds are relatively low but the area on which the surface force acts and its moment arm are both high. Intriguingly the higher surface forces arise also from the higher winds predicted by the new code. An interesting finding is that, on both track and minimum pressure, the improvement due to higher resolution is greater with the new boundary layer module. Further analysis is necessary to assess the effect of other eddy fluxes (sensible heat, moisture) on cyclone track prediction.